A Liquid Biopsy to Assess Brain Tumor Recurrence: Presence of Circulating Mo-MDSC and CD14+ VNN2+ Myeloid Cells as Biomarkers That Distinguish Brain Metastasis From Radiation Necrosis Following Stereotactic Radiosurgery. Issue 1 (21st August 2020) - Soler, David C; Kerstetter-Fogle, Amber; Elder, Theresa; Raghavan, Alankrita; Barnholtz-Sloan, Jill S; Cooper, Kevin D; McCormick, Thomas S; Sloan, Andrew E
Abstract: BACKGROUND: Brain metastases (BM) are the most common type of brain tumor malignancy in the US. They are also the most common indication for stereotactic radiosurgery (SRS). However, the incidence of both local recurrence and radiation necrosis (RN) is increasing as treatments improve. MRI imagery often fails to differentiate BM from RN; thus, patients must often undergo surgical biopsy or resection to obtain a definitive diagnosis. OBJECTIVE: To hypothesize that a marker of immunosuppression might serve as a surrogate marker to differentiate patients with active vs inactive cancer—including RN. METHODS: We thus purified and quantified Monocytic Myeloid-Derived Suppressor Cells (Mo-MDSC) by flow cytometry in patients proven by biopsy to represent BM or RN. RESULTS: We report the utility of the previously reported HLA-Dr-Vnn2 Index or DVI to discriminate recurrent BM from RN using peripheral blood. The presence of CD14 + HLA-DR neg/low Mo-MDSC is significantly increased in the peripheral blood of patients with brain metastasis recurrence compared to RN (Average 61.5% vs 7%, n = 10 and n = 12, respectively, P  < .0001). In contrast, expression of VNN2 on circulating CD14 + monocytes is decreased in BM patients compared to patients with RN (5.5% vs 26.5%, n = 10 and n = 12, respectively, P  = .0008). In patients with biopsy confirmed recurrence of brain metastasis, the average DVI was 11.65, whereas the average DVI for RN patients was consistently <1 (Avg. of 0.17). CONCLUSION: These results suggest that DVI could be a useful diagnostic tool to differentiate recurrent BM from RN using a minimally invasive blood sample.